Centro y periferia: La propagación de la crisis global a las economías de la región - Sebastián Katz; Eduardo Corso (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2010)
– Although the international crisis was initially seen as an event limited to a particular segment of the financial systems of central economies, it rapidly escalated and became global through different transmission channels, raising doubts over the hypothesis of the so-called decoupling. Latin American economies faced this new scenario under more robust conditions than in the past episodes of crisis. The good macroeconomic performance of the region during the five-year period prior to the onset of the crisis reduced the vulnerability of these economies and increased the degrees of freedom of economic policy authorities to implement counter-cyclical policies in the new international context. Despite the efforts made by these economies, a comprehensive policy response will require a commitment of resources and coordination by the main developed economies. In this sense, policy challenges are not limited to emerging economies: they imply a global coordination effort.
Keywords: E60; F42; F44; G01; 330; center and periphery; counter-cyclical policies; emerging economies; international crisis; Latin America; transmission mechanisms